Роль культурфітоценозів Волинської області у збереженні раритетних деревних рослин - Коцун, Лариса Олександрівна; Кузьмішина, Ірина Іванівна; Коцун, Борис Борисович; Kotsun, Larysa O.; Kuzmishyna, Iryna I.; Kotsun, Borys B. (Ботанічний сад імені акад. О.В. Фоміна Київського національного університету імені Тараса Шевченка, 2016)
In the aim to preserve the phytobiota diversity of artificial environmental objects and valuable centers of cultivated dendroflora of Volyn region the importance of rarity dendrobiotic variety isestablished. Data of 25 species of woody plants with different protection status from cultivated dendroflora objects is obtained. The dendro-sozological monitoring necessity is shown.
Role of Volyn region сulturephytocoenosis in the preservation of rare woody
Keywords: культивована дендрофлора; Волинська область; раритетні види рослин